A randomized, placebo‐controlled trial of cenicriviroc for treatment of nonalcoholic steatohepatitis with fibrosis - Friedman, Scott L.; Ratziu, Vlad; Harrison, Stephen A.; Abdelmalek, Manal F.; Aithal, Guruprasad P.; Caballeria, Juan; Francque, Sven; Farrell, Geoffrey; Kowdley, Kris V.; Craxi, Antonio; Simon, Krzysztof; Fischer, Laurent; et al. (Hepatology (Baltimore, Md.), 2018)
The aim of this study was to evaluate cenicriviroc (CVC), a dual antagonist of CC chemokine receptor types 2 and 5, for treatment of nonalcoholic steatohepatitis (NASH) with liver fibrosis (LF). A randomized, double‐blind, multinational phase 2b study enrolled subjects with NASH, a nonalcoholic fatty liver disease activity score (NAS) ≥4, and LF (stages 1‐3, NASH Clinical Research Network) at 81 clinical sites. Subjects (N = 289) were randomly assigned CVC 150 mg or placebo. Primary outcome was ≥2‐point improvement in NAS and no worsening of fibrosis at year 1. Key secondary outcomes were: resolution of steatohepatitis (SH) and no worsening of fibrosis; improvement in fibrosis by ≥1 stage and no worsening of SH. Biomarkers of inflammation and adverse events were assessed. Full study recruitment was achieved. The primary endpoint of NAS improvement in the intent‐to‐treat population and resolution of SH was achieved in a similar proportion of subjects on CVC (N = 145) and placebo (N = 144; 16% vs. 19%, P = 0.52 and 8% vs. 6%, P = 0.49, respectively). However, the fibrosis endpoint was met in significantly more subjects on CVC than placebo (20% vs. 10%; P = 0.02). Treatment benefits were greater in those with higher disease activity and fibrosis stage at baseline. Biomarkers of systemic inflammation were reduced with CVC. Safety and tolerability of CVC were comparable to placebo. Conclusion: After 1 year of CVC treatment, twice as many subjects achieved improvement in fibrosis and no worsening of SH compared with placebo. Given the urgent need to develop antifibrotic therapies in NASH, these findings warrant phase 3 evaluation. (Hepatology 2018;67:1754‐1767).